Sexism, attitudes, and behaviors towards violence against women in medical emergency services workers in Erzurum, Turkey - Elif Okşan Çalıkoglu; Aysun Aras; Maysa Hamza; Ayşegül Aydin; Onur Nacakgedigi; Patrick Marius Koga (Taylor & Francis Group, 2018)
Background: In Turkey, almost every 4 out of 10 married women have been subjected to physical abuse by their spouses. Although studies on the prevalence of domestic violence in Turkey abound, little has been published about first responders' attitudes and behaviors towards violence against women and on sexism. Objective: Our study examined the attitudes and behaviors of Erzurum City medical emergency services workers towards violence against women, and their relationship with sexist attitudes. Methods: A cross-sectional survey was conducted among 370 medical emergency service personnel using a self-administered questionnaire of 35 items, which included two scales utilizing a three-point Likert format; 15 questions measured attitudes and behaviors towards violence against women (VAW) and 12 items measured sexist attitudes. Results: The mean age of participants was 29.6 ± 8.0 years with a sex distribution of (47.6%) women and 194 (52.4%) men. Less than half of the participants (48.5%; n = 173) felt competent in recognizing and managing VAW; moreover, when faced with such cases, 18.5% (n = 67) said they would try to reconcile the victim with the perpetrator. Male participants had higher mean scores both on VAW (20.7 ± 5.2 vs. 16.9 ± 2.8; t = 7.927; p < 0.001) and on sexist attitudes (24.3 ± 5.3 vs. 18.6 ± 4.3; t = 1.714; p < 0.001). Age (B = 0.067; 95% CI: 0.014-0.119; p = 0.013) and sexism scores (B = 0.487; 95% CI: 0.407-0.566; p < 0.001) were revealed as independent significant predictors of the VAW attitude scores. Conclusions: Educational and public health measures must be instituted to change attitudes and behaviors towards violence against women; measures must focus not only on violence but also on sexism. Health care professionals need to reflect on their own gender biases in clinical practice and prevent gender discrimination.